Transcriptomics and Antioxidant Analysis of Two Chinese Chestnut (Castanea mollissima BL.) Varieties Provides New Insights Into the Mechanisms of Resistance to Gall Wasp Dryocosmus kuriphilus Infestation - Zhu, Cancan; Wang, Wu; Chen, Yu; Zhao, Yuqiang; Zhang, Shijie; Shi, Fenghou; Khalil-Ur-Rehman, Muhammad; Nieuwenhuizen, Niels J. (Frontiers in Plant Science, 2022)
Chinese chestnut is a popular fruit tree with a high nutritional value of its nuts, which can suffer from infestation by the chestnut gall wasp Dryocosmus kuriphilus (GWDK) that results in gall formation and resultant loss of production and profitability. The physiological and molecular mechanisms of GWDK resistance found in certain genotypes currently remains elusive. To gain new insights into this phenomenon, a series of RNA-Seq integrated with metabolomic profiling experiments were executed to investigate the chemical and transcriptional differences in response to GWDK infestation in two contrasting chestnut varieties grown in China (the susceptible “HongLi,” HL and the partially resistant “Shuhe_Wuyingli,” SW). Three time points were selected for comparison: The initiation stage (A), growth stage (B), and maturation stage (C). Results showed that concentrations of hydrogen peroxide (H2O2) and the activities of peroxidase (POD) and superoxide dismutase (SOD) enzyme were elevated in the resistant SW leaves compared with those in HL leaves at all three developmental stages, while catalase (CAT) and polyphenol oxidase (PPO) activities were mostly higher in HL leaves. RNA-Seq transcriptomic analyses of HL and SW leaves revealed that various metabolic pathways involved in GWDK stress responses, such as plant hormone signal transduction, MAPK signaling, and the peroxisome pathway, were enriched in the contrasting samples. Moreover, the weighted gene co-expression network analysis (WGCNA) of differentially expressed genes in the POD pathway combined with transcription factors (TFs) indicated that the expression of TF members of bHLH, WRKY, NAC, and MYB family positively correlated with POD pathway gene expression. The TFs CmbHLH130 (EVM0032437), CmWRKY31 (EVM0017000), CmNAC50 (EVM0000033), and CmPHL12 (EVM0007330) were identified as putative TFs that participate in the regulation of insect-induced plant enzyme activities in chestnut, which may contribute to GWDK resistance in SW. Expression levels of 8 random differentially expressed genes (DEGs) were furthermore selected to perform quantitative reverse transcription PCR (qRT-PCR) to validate the accuracy of the RNA-Seq-derived expression patterns. This study guides the functional analyses of further candidate genes and mechanisms important for GWDK resistance in chestnuts in the future as well as can help in identifying the master transcriptional regulators and important enzyme steps that support major insect defense pathways in chestnut.